From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Holocene overflow events of the lower Yellow River recorded in Huangdun ancient lake, northern Jiangsu Plain, China - Rui Zhang; Li Xing; Shi‐Yong Yu; Junsheng Nie; Jinjia Wu; Zhao Wang; Shiyue Chen; Zhanfang Hou; Guodong Zhang; Denghui Zhang (Journal of Quaternary Science, 2024)
Overflow events are important embodiments of the evolutionary characteristics of the lower Yellow River. Lakes in the lower reaches of the Yellow River have the capacity to record these events. Due to the complex provenance and transport pathways of sediments in local lakes, it is difficult to extract reliable information on sediments delivered by the Yellow River based on conventional methods and proxies. Here, we show results from a genetically meaningful end‐member (EM) decomposition of sediment grain‐size data from Huangdun ancient lake. The grain‐size of the sediments can be decomposed into three end‐members. Comprehensive analysis combining environmental magnetism and geochemical indicators clarifies the significance of each end‐member. EM1 represents mixed signals of various proximal fluvial sediments and the Yellow River materials. EM2 is similar to terrestrial fine‐grained debris in conjunction with local pedogenic materials, aeolian inputs and some Yi River materials. EM3 represents a component that is mainly derived from long‐distance transport by the lower Yellow River. End‐member analysis successfully identified overflow events of the lower Yellow River on a southward‐flowing path during the Holocene. This study provides a meaningful attempt to reconstruct the evolutionary history of the lower Yellow River from sedimentary records.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.